Outbreaks of the measles in the Dutch Bible Belt and in other places – New prospects for a 1000 year old virus. (March 2019) - Lisowski, Bartosz; Yuvan, Steven; Bier, Martin
Abstract: In the Netherlands there has been nationwide vaccination against the measles since 1977. However, a tight-knit community of a few hundred thousand orthodox protestants in the "Dutch Bible Belt" refuses the vaccine. Within this community of orthodox protestants there has been an outbreak of the measles with roughly 2500 reported cases about every twelve years. Each outbreak has lasted about a year. The community of orthodox protestants is too small to permanently keep the virus in circulation and have the infection be endemic. The dynamics in orthodox-protestant schools has been widely recognized as the engine behind the epidemic outbreaks. It is shown how these dynamics are a kind of integrate-and-fire mechanism: new susceptibles enter the denominational schools until a critical mass is reached and an outbreak occurs. From a public health perspective, periodic outbreaks of the measles are worse than an endemic situation. When the measles was endemic, almost every child would get infected at around the age of ten. This is also the age at which one is best able to cope with the disease. With the short periodic outbreaks, a significant fraction of the orthodox-protestant, schoolgoing population does not get infected during an outbreak. These "escapees, " however, may then get infected during a next outbreak when they are adults and less well-equipped to handle the disease. The three subsequent outbreaks in the Dutch Bible Belt (1988, 1999, 2013) have indeed shown increasingly many adult cases and hospitalizations. As vaccination rates in the developed world are decreasing, the situation in the Dutch Bible Belt is duplicated in other places. We point out how in some large European cities the relevant parameters resemble those in the Dutch Bible Belt. We, furthermore, provide extensive background on the thousand year relation between humanity and the measles virus.